Stern-Gerlach splitting of low-energy ion beams - Henkel, Carsten; Jacob, Georg; Stopp, Felix; Schmidt-Kaler, Ferdinand; Keil, Mark; Japha, Yonathan; Folman, Ron (New Journal of Physics, 2019)
We present a feasibility study with several magnetic field configurations for creating spin-dependent forces that can split a low-energy ion beam by the Stern-Gerlach (SG) effect. To the best of our knowledge, coherent spin-splittings of charged particles have yet to be realised. Our proposal is based on ion source parameters taken from a recent experiment that demonstrated single-ion implantation from a high-brightness ion source combined with a radio-frequency Paul trap. The inhomogeneous magnetic fields can be created by permanently magnetised microstructures or from current-carrying wires with sizes in the micron range, such as those recently used in a successful implementation of the SG effect with neutral atoms. All relevant forces (Lorentz force and image charges) are taken into account, and measurable splittings are found by analytical and numerical calculations.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Beam splitter; Ion optics; Magnetic microstructures; Spin-dependent forces; Stern-gerlach effect